Habitat, hábito e morfologia cardíaca: influência destes fatores sobre as respostas cardiorrespiratórias à hipóxia e alterações térmicas em espécies de peixes ecologicamente distintas - Thomaz, Juliana Montovani (Universidade Federal de São Carlos, 2011)
Aquatic environments are subjected to wide variations in their physicochemical properties which can compromise the survival of the animals that inhabit these waters, especially the fish, which exhibit adaptive behavioral, physiological, biochemical and genetic responses to face such variations. The aim of the present study was to assess the relationship between heart morphology and the cardiorespiratory responses to hypoxia at different temperatures (15, 25 and 35 °C) of two fish species with different habits and habitats: matrinxã (Brycon amazonicus) and trahira (Hoplias malabaricus). Both species presented pyramidal ventricles with compact and spongy layers (mixed myocardium), differentiated by the thickness of the compact layer and its irrigation, which occurs in greater proportion in matrinxã, the active species. Gradual temperature reductions decreased the values of metabolic rate ( ̇ ), gill ventilation ( ̇ ), respiratory frequency (fR), ventilatory volume (VT), and heart rate (fH) while increases in temperature induced opposite responses, increasing the values of these parameters. In matrinxã and trahira, the gradual reduction in the water O2 concentration at different temperatures induced significant changes in the cardiorespiratory parameters. The combined effects of low temperature (15 °C) and hypoxia led to a significant reduction in ̇ , ̇ , fR, VT, EO2 (O2 extraction) and fH, while high temperature (35 °C) and hypoxia led to a significant increase in these parameters. The results showed that temperature acts in the overall metabolism of fish as well as in myocardial metabolism and membrane permeability to the ions involved in their polarity. Moreover, the active species matrinxã presented higher values of cardiorespiratory parameters and a lower tolerance to hypoxia when compared to trahira, the sedentary species.
Keywords: Fisiologia; Brycon amazonicus; Hipóxia; Hoplias malabaricus; Eletrocardiograma; Respirometria; Brycon amazonicus; Cardiac morphology; Electrocardiogram; Hypoxia; Hoplias malabaricus; Metabolic rate; Respirometry; Ventilatory parameters; CIENCIAS BIOLOGICAS::FISIOLOGIA